Educating the enemy: Harnessing learned avoidance behavior in wild predators to increase survival of reintroduced southern corroboree frogs. Issue 1 (9th December 2019) - Umbers, Kate D. L.; Riley, Julia L.; Kelly, Michael B. J.; Taylor‐Dalton, Griffin; Lawrence, Justin P.; Byrne, Phillip G.
Abstract: After decades of near‐complete extirpation, the yellow‐and‐black‐striped Southern Corroboree Frog ( Pseudophryne corroboree ) is being reintroduced into field enclosures that exclude all but avian predators. The frog's long absence means avian attack risk to reintroduced individuals is unknown, so we asked: does corroboree frog coloration make them vulnerable to predators? First, using painted clay frog models and humans as proxy predators, we found that, surprisingly, striped models were as difficult to detect as control black models, and were far less detectable than yellow models. Second, to quantify attack probabilities, we deployed 2, 304 models twice in the species' former range. Of our recovered models, 18% of the striped models were attacked by birds, suggesting they are a significant threat. In our second deployment, we saw a significant reduction in attacks on all model colors with only 10% of striped models attacked. If predators generalize their avoidance learning to real corroboree frogs, strategically timed model deployment near release sites may enhance the probability of survival of reintroduced frogs. Our study suggests that model deployment could be an effective low‐cost technique to increase the survival of reintroduced prey species, including, but not limited to, those potentially conspicuous to their natural enemies. Abstract :